A Cross-Sectional Study on Cerebral Hemodynamics After Mild Traumatic Brain Injury in a Pediatric Population - Thibeault, Corey M.; Thorpe, Samuel; O’Brien, Michael J.; Canac, Nicolas; Ranjbaran, Mina; Patanam, Ilyas; Sarraf, Artin; LeVangie, James; Scalzo, Fabien; Wilk, Seth J.; Diaz-Arrastia, Ramon; Hamilton, Robert B. (Frontiers in Neurology, 2018)
The microvasculature is prominently affected by traumatic brain injury (TBI), including mild TBI (concussion). Assessment of cerebral hemodynamics show promise as biomarkers of TBI, and may help inform development of therapies aimed at promoting neurologic recovery. The objective of this study was to assess the evolution in cerebral hemodynamics observable with transcranial Doppler (TCD) ultrasound in subjects suffering from a concussion at different intervals during recovery. Pediatric subjects between the ages of 14 and 19 years clinically diagnosed with a concussion were observed at different points post-injury. Blood flow velocity in the middle cerebral artery was measured with TCD. After a baseline period, subjects participated in four breath holding challenges. Pulsatility Index (PI), Resistivity Index (RI), the ratio of the first two pulse peaks (P2R), and the mean velocity (MV), were computed from the baseline section. The Breath Hold Index (BHI) was computed from the challenge sections. TCD detected two phases of hemodynamic changes after concussion. Within the first 48 hours, PI, RI, and P2R, show a significant difference from the controls (U = −3.10; P < 0.01, U = −2.86; P < 0.01, and U = 2.62; P < 0.01, respectively). In addition, PI and P2R were not correlated (rp = −0.36; P = 0.23). After 48 hours, differences in pulsatile features were no longer observable. However, BHI was significantly increased when grouped as 2-3, 4-5, and 6-7 days post-injury (U = 2.72; P < 0.01, U = 2.46; P = 0.014, and U = 2.38; P = 0.018, respectively). To our knowledge, this is the first longitudinal study of concussions using TCD. In addition, these results are the first to suggest the multiple hemodynamic changes after a concussion are observable with TCD and could ultimately lead to a better understanding of the underlying pathophysiology. In addition, the different hemodynamic responses to a concussion as compared to severe traumatic brain injuries highlights the need for specific diagnostic and therapeutic treatments of mild head injuries in adolescents.